How to resolve conflict in organizations : the power of people models and procedure - Garden, Anna-Maria (Routledge, Taylor & Francis Group, 2018)
This is a comprehensive guide using People Models to understand and resolve conflict at different levels of the organization. It starts at the inter-organizational level explaining conflict between organizations that are involved in mergers and acquisitions. It looks at this kind of conflict not from the point of view of a business and economic rationale but from the point of view of there being a relationship between the two organizations. Here, this relationship is described by a People Model which outlines three different relationship types. In the subsequent chapters we look at the organizational level; first at structural conflict and then at team conflict. In each chapter there is a People Model to explain and resolve conflict. Structural conflict is explained by the Myers Briggs Type Indicator (MBTI) and team conflict is explained by the Schutz model of Inclusion, Control and Openness. In the next chapter the conflict is explained in terms of Gestalt psychology and looks at interpersonal conflict. Carl Jung is then used to explore inner conflict; followed by a chapter on life conflict exploring conflict in terms of how you live a life. The final chapter is focused on the applications of the People Models analysing Donald Trump and Tony Blair. Following through the entire book is a step-by-step procedure called a People Procedure, which is contrasted with a Business Procedure. The former guides you through a process to unravel and resolve conflict.